2009
DOI: 10.1002/ejoc.200801234
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of the C11–C23 Fragment of the Potent Antitumor Agent Dictyostatin

Abstract: Descrevemos neste trabalho uma síntese curta e eficiente para o fragmento C1-C9 do potente agente antitumoral dictiostatina. Esta abordagem sintética inclui uma reação de epoxidação assimétrica de Sharpless seguida da abertura de epóxido nas condições de Myashita para introduzir os centros estereogênicos em C6 e C7 e uma reação de olefinação tipo Horner-Wadsworth-Emmons nas condições de Ando para construir a ligação com geometria /Z/do dieno 1,3-/Z/,/E/.We describe herein a short and efficient synthesis of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…R f = 0.36 (20 % EtOAc in hexane). [ α ] D 20 = +8.0 ( c = 1.02, CHCl 3 ) 24 . 1 H NMR (250 MHz, C 6 D 6 ): δ = 0.10 (s, 3 H), 0.14 (s, 3 H), 1.02 (s, 9 H), 1.18 (d, J = 7.0 Hz, 3 H), 1.34 (d, J = 7.0 Hz, 3 H), 2.27–2.18 (m, 1 H), 2.86 (s, 3 H), 3.08 (br.…”
Section: Methodsmentioning
confidence: 99%
“…R f = 0.36 (20 % EtOAc in hexane). [ α ] D 20 = +8.0 ( c = 1.02, CHCl 3 ) 24 . 1 H NMR (250 MHz, C 6 D 6 ): δ = 0.10 (s, 3 H), 0.14 (s, 3 H), 1.02 (s, 9 H), 1.18 (d, J = 7.0 Hz, 3 H), 1.34 (d, J = 7.0 Hz, 3 H), 2.27–2.18 (m, 1 H), 2.86 (s, 3 H), 3.08 (br.…”
Section: Methodsmentioning
confidence: 99%
“…The cells were thereafter washed twice with phosphate buffered saline (PBS) to remove detached cells. Growth media was then added containing different concentrations of the chemical compound and incubated at 37 • C. 28 The cells were photographed at the beginning of the experiment and after 24 and 48 h to assess the progression of cell migration into the wound. 29,30 Chamber cell-migration assay.…”
Section: Materials and Methods (For Human Cancer Cell Studies)mentioning
confidence: 99%
“…In addition, it is important to note that the ferrocenyl oxindoles studied are structurally simple and easily accessible, therefore representing new potential lead compounds for further development in cancer therapy. 27,28 Experimental IR spectra were recorded on a Nicolet Magna 760 (KBr). 1 H-and 13 C-NMR were recorded on Bruker 250 or 500 MHz spectrometers.…”
Section: Biological Evaluationmentioning
confidence: 99%
“…Lactone 2 used in the NMR studies was an authentic sample synthesised according to the method described in ref. 7. Data of 2: R f 0.12 (15% EtOAc-hexane); [α] 20 D = −60 (c = 1.6, CHCl 3 ); for 1 H and 13 C NMR spectra see Table 1.…”
Section: Synthesismentioning
confidence: 99%
“…6 As part of similar synthetic efforts, the Dias group disclosed the synthesis of the C11-C23 fragment of dictyostatin employing the 3-epi-Prelog-Djerassi lactone derivative (2) as a key intermediate. 7 It was observed that the H-5 methylene of compound 2 presented an anomalous 1 H chemical shift difference (1.02 and 2.54 ppm, Δδ = 1.52 ppm). In general, the chemical shifts of diastereotopic H-5 protons for the Prelog-Djerassi lactone (1) and its derivatives are in the range of 1.2 to 2.0 ppm (Δδ = 0.8 ppm).…”
Section: Introductionmentioning
confidence: 99%